Crocodile Rock! A Bioarchaeological Study of Ancient Egyptian Reptile Remains from the National Museum of Lithuania - Piombino-Mascali, Dario; Jankauskas, Rimantas; Piličiauskienė, Giedrė; Girčius, Rokas; Ikram, Salima; Caliò, Luigi M.; Messina, Antonio (Archaeologia Lituana, 2024)
Remnants of what was believed to be a single baby crocodile, originating from ancient Egypt and curated in the National Museum of Lithuania, have been recently assessed using noninvasive and nondestructive techniques. These had been donated in 1862 to the then Museum of Antiquities by the prominent Polish-Lithuanian collector Count Michał Tyszkiewicz. After careful investigation of the three mummified reptile fragments available, the authors were able to identify at least two individuals based on morpho-anatomical characteristics. This indicates that the two small crocodiles originally described in historic records are still present within the collection and that none of these items was lost during the different lootings perpetrated throughout the museum’s history. Information regarding the post-mortem treatment of these animals was also obtained. This is the first scientific study of animal mummies in the Baltic States, and it should be followed by proper conservation and display of these findings.